THE INFLUENCE OF SUNDAY WORSHIP SERVANTS ON THE ATTENDANCE OF THE GPdI BETHANI MEDAN WEAVING FACTORY CONGREGATION IN 2023 - Samuel Butar-butar (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
The servants in the church are people chosen by God to serve and who are able to be responsible in every service entrusted to them. The purpose of the study was to determine whether there was an influence of the Sunday worship servants on the attendance of the GPdI Bethani Pabrik Tenun Medan congregation in 2023. This type of research was quantitative descriptive with a simple linear regression approach. The population was 220 people, and the research sampling technique was carried out by random sampling, namely 69 people, with a partial test (t test) with a confidence level of 95% (α = 0.05). The results of the study showed that the correlation between the worship system and congregation attendance was relative but significant with a calculated t value of -.586> t table 0.236, which means the hypothesis was accepted, namely Ho was rejected and H1 was accepted.